Analisis Faktor-Faktor Yang Mempengaruhi Kualitas Hasil Audit Di Lingkungan Pemerintah Daerah (Studi Empiris Pada Inspektorat Tingkat Kota/Kabupaten Di Surakarta Dan Sukoharjo) - Hadi, Hari, Dra Rina Trisnawati, Ak, M.Si,Ph.D Co. I (2014)
This study aimed to analyze the factors that affect the quality of the audit results in the Local Government Inspectorate is the city of Surakarta and Sukoharjo Inspectorate. Factors examined in this paper is work experience, independence, objectivity, integrity and knowledge. The population in this study are all Civil Servants (PNS) who works at the level Inspectorate City / County in Surakarta and Sukoharjo. The sampling method in this study using purposive sampling approach. With the sample used by 50 civil servants (PNS) which works on the level Inspectorate City / County as respondents. The analysis tool used is multiple linear regression, the coefficient of determination, F test, T-test and classical assumption. These results indicate that the integrity and knowledge of a positive effect on the quality of the audit results in the Local Government. Meanwhile, work experience, independence and objectivity does not significantly influence the quality of the audit results in the Local Government.